Pemberdayaan Keluarga dengan Pendekatan Health Coaching pada Keluarga Sadar dan Siaga Tuberculosis Paru di Wilayah Kerja Puskesmas Payo Selincah - Mila Triana Sari; Miko Eka Putri; Daryanto Daryanto; Jufri Al Fajri; Apriyali Apriyali; Selda Vigri; Misyina Misyina (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Pulmonary tuberculosis is very contagious, and can have a negative impact on family members who live in the same household as someone with pulmonary tuberculosis. Families who live with pulmonary TB clients are very vulnerable to infection because of the lack of knowledge about preventing pulmonary TB transmission. Payo Selincah Health Center is ranked 3rd for pulmonary TB cases out of 24 health centers in Jambi City, with a significant increase in cases every year. The main cause of the high cases of pulmonary TB in the work area of the Payo Selincah Health Center is the lack of adherence to treatment and behavior to prevent transmission in the family. The purpose of this community service is a movement to empower families with pulmonary TB awareness and alertness and increase the ability and independence of families in treating and preventing pulmonary TB transmission with a Health Coaching approach. Activities carried out in the form of socialization, pre-test, health counseling using power points and leaflets, demonstration of how to cough and expel phlegm correctly, companion to take medicine, post-test and assistance to families whose family members suffer from pulmonary TB. The activity was attended by 26 people, consisting of village officials, health workers, community leaders, cadres and families. The result of this activity is an increase in the knowledge and ability of the community and families in caring for and preventing the transmission of pulmonary TB with a difference of 38.0% in the pre and post test scores. In conclusion, empowering the sasiga family with the Health Coaching method and health education for families is effective in increasing knowledge and ability in treating and preventing pulmonary TB transmission, Primary Health Care should optimize the TB TOSS program and mentoring with Whatsapp group, so that it will break the chain of pulmonary TB spread in the family. and improve recovery for patients with pulmonary TB.